STUDY ON APPLICATION OF TOURISTIFICATION CONCEPT IN LIKUPANG TOURISM SEZ DEVELOPMENT PLAN - Putro, Heru Purboyo Hidayat; Azkarifa, Shofi (ASEAN Journal on Hospitality and Tourism, 2020)
This paper examine the concept of touristification that positions tourists and the community as key actors in the process of tourism growth. The authors apply the concept in Likupang Special Economic Zone (SEZ) tourism area development plan. The area chosen due to its top priority to tourism destinations development plan. Likupang SEZ has the potential for bottom-up tourism development that can be seen from the role of the community. The concept review conducted on the Likupang SEZ was seen from the growth in the number of tourists, the role of the community, and the potential for regional transformation. The study, founds that tourists have a significant role in encouraging tourism development policies and physical changes in the tourism area. Meanwhile, the community has the potential to be the key to tourism growth going forward with the encouragement of facilities from the government. The area has the potential to transform into an area of tourism with a variety of activities. However, based on the review conducted, currently, the transformation that is expected to occur comes from the encouragement of investment from the private sector and also the government (top-down).